Investigation of Heat Exchanger Performance in The Heating Tank Section of Loop FASSIP 03 NT - Haryanto, Dedy; Budiman, Arif Adtyas; Putra, Muhammad Ganjar; Setiawan, Putut Hery; Juarsa, Mulya (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
The Passive System Simulation Facility (FASSIP) loop is an experimental test facility for a passive cooling system to recover the residual heat from decay produced by the reactor core during accident conditions. The Heating Tank Section (HTS) is one of the components of the FASSIP 03 NT facility. This component is equipped with a heat exchanger, 3 types of heat exchangers can be applied to HTS. Namely heat exchangers of the Straight Pipe Heat Exchanger (SPHE) type, the Straight Pipe Fins Heat Exchanger (SPFHE) type, and the Helical Pipe Heat Exchanger (HPHE) type. A modification was made to increase the efficiency of HTS, namely replacing the electric heater on the HTS from a ceramic band heater type to an immersion heater type. With this modification, it is necessary to know the performance of the heat exchanger on HTS and its speed in reaching operational temperature. The HPHE-type heat exchanger is more efficient than the SPHE-type and SPFHE-type heat exchangers. The HPHE-type heat exchanger has a much larger length of 5.5 m, so the thermal resistance (Rth) is very small, namely 0.003926 ℃/W. To reach the working fluid temperature in the range of 50 – 90 ℃, the HPHE-type heat exchanger requires 35 – 86 minutes.